Application of Simple Plane Cap Model to Simulate Compression Failure of RC Beam under Impact Loads - Mokhatar, Shahrul Niza; Sonoda, Yoshimi; Kamarudin, Ahmad Fahmy (International Journal of Sustainable Construction Engineering and Technology, 2020)
The aim of this paper is to present the non-linear analysis for impact response of reinforced concrete (RC) beam with prominence on tension and compression area. In order to envisage the RC behavior, pressure dependant yield criteria Drucker-Prager Plane-Cap (DPPC) type is assumed for the concrete, meanwhile, shear strain energy criterion Von-Mises (VM) is applied for steel reinforcement; to define the accurate strength of material during the short period (dynamic). These material models were incorporated with Adaptive Smoothed Particle Hydrodynamics (ASPH) method. Dynamic Increase Factor (DIF) has been employed for the effect of strain rate (SR) on the compression and tensile strength of the concrete; the orthotropic constitutive equation due to the damage effect is considered during the softening phase on tensile region while constitutive equation of cap model is employed on compression area. A series of experimental studies were also presented in this paper. Several beam elements were tested under low velocity impact loads. Failure mechanism such as shear cracking, bending cracking, compressive behavior of the beam were evaluated by using displacement-time histories as well as overall failure mode. Based on these studies, the investigations enabled a better understanding of the behavior of reinforced concrete beam elements under low velocity impact loads, as well as, it is confirmed that the proposed models give good agreement with experimental results.